Co-localisation of the Kir6.2/SUR1 channel complex with glucagon-like peptide-1 and glucose-dependent insulinotrophic polypeptide expression in human ileal cells and implications for glycaemic control in new onset type 1 diabetes. - Nielsen, L; Ploug, K; Swift, P; Ørskov, C; Jansen-Olesen, I; Chiarelli, F; Holst, J; Hougaard, P; Pörksen, S; Holl, R; de Beaufort, C; Gammeltoft, S; et al. (2007)
OBJECTIVE: The ATP-dependent K+-channel (K(ATP)) is critical for glucose sensing and normal glucagon and insulin secretion from pancreatic endocrine alpha- and beta-cells. Gastrointestinal endocrine L- and K-cells are also glucose-sensing cells secreting glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotrophic polypeptide (GIP) respectively. The aims of this study were to 1) investigate the expression and co-localisation of the K(ATP) channel subunits, Kir6.2 and SUR1, in human L- and K-cells and 2) investigate if a common hyperactive variant of the Kir6.2 subunit, Glu23Lys, exerts a functional impact on glucose-sensing tissues in vivo that may affect the overall glycaemic control in children with new-onset type 1 diabetes. DESIGN AND METHODS: Western blot and immunohistochemical analyses were performed for expression and co-localisation studies. Meal-stimulated C-peptide test was carried out in 257 children at 1, 6 and 12 months after diagnosis. Genotyping for the Glu23Lys variant was by PCR-restriction fragment length polymorphism. RESULTS: Kir6.2 and SUR1 co-localise with GLP-1 in L-cells and with GIP in K-cells in human ileum tissue. Children with type 1 diabetes carrying the hyperactive Glu23Lys variant had higher HbA1C at diagnosis (coefficient = 0.61%, P = 0.02) and 1 month after initial insulin therapy (coefficient = 0.30%, P = 0.05), but later disappeared. However, when adjusting HbA1C for the given dose of exogenous insulin, the dose-adjusted HbA1C remained higher throughout the 12 month study period (coefficient = 0.42%, P = 0.03). CONCLUSIONS: Kir6.2 and SUR1 co-localise in the gastrointestinal endocrine L- and K-cells. The hyperactive Glu23Lys variant of the K(ATP) channel subunit Kir6.2 may cause defective glucose sensing in several tissues and impaired glycaemic control in children with type 1 diabetes.